Low power dissipation SiGe HBT dual-band variable gain amplifier. Issue 7 (July 2015) - Xie, Hongyun; Liu, Shuo; Zhang, Lianghao; Jiang, Zhiyun; Zhao, Yanxiao; Chen, Liang; Zhang, Wanrong
Abstract A dual-band variable gain amplifier operating at 0.9 GHz and 2.4 GHz was designed based on high performance RF SiGe HBT for large amount of signals transmission and analysis. Current steering was adopted in gain-control circuit to get variable trans-conductance and then variable gain. Emitter degeneration and current reuse were considered in amplifying stage for low noise figure and low power dissipation respectively. A single-path circuit resonating at two frequency points simultaneously was designed for input impedance matching. PCB layout parasitic effects, especially the via parasitic inductor, were analyzed theoretically and experimentally and accounted for using electro-magnetic (EM) simulation. The measurement results show that a dynamic gain control of 26 dB/16 dB in a control voltage range of 0.0–1.4 V has been achieved at 0.9/2.4 GHz respectively. Both S11 and S22 are below than –10 dB in all the control voltage range. Noise figures at both 0.9 GHz and 2.4 GHz are lower than 5 dB. Total power dissipation of the dual-band VGA is about 16.5 mW at 3 V supply.